1994
DOI: 10.1017/s0022112094002703
|View full text |Cite
|
Sign up to set email alerts
|

Particle response and turbulence modification in fully developed channel flow

Abstract: The interactions between small dense particles and fluid turbulence have been investigated in a downflow fully developed channel in air. Particle velocities of, and fluid velocities in the presence of, 50 μm glass, 90 μm glass and 70 μm copper spherical beads were measured by laser Doppler anemometry, at particle mass loadings up to 80%. These particles were smaller than the Kolmogorov lengthscale of the flow and could respond to some but not all of the scales of turbulent motion. Streamwise mean particle velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
301
3
10

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 534 publications
(355 citation statements)
references
References 15 publications
34
301
3
10
Order By: Relevance
“…The phenomenon has been observed experimentally in pipe flows (Tsuji et al 1984), channel flows (Kulick, Fessler & Eaton 1994;Kussin & Sommerfeld 2002) and stationary homogeneous turbulence (Hwang & Eaton 2006;Tanaka & Eaton 2010). These works clearly show that the turbulence kinetic energy of the carrier phase of a turbulent flow laden with small particles is lower than in the corresponding unladen flow.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The phenomenon has been observed experimentally in pipe flows (Tsuji et al 1984), channel flows (Kulick, Fessler & Eaton 1994;Kussin & Sommerfeld 2002) and stationary homogeneous turbulence (Hwang & Eaton 2006;Tanaka & Eaton 2010). These works clearly show that the turbulence kinetic energy of the carrier phase of a turbulent flow laden with small particles is lower than in the corresponding unladen flow.…”
Section: Introductionmentioning
confidence: 69%
“…Kulick et al (1994) measured strong turbulence attenuation in a gas-solid turbulent channel flow with a particle volume fraction of 0.0001, particle size d + p = 2.3 and Re τ = 640. Recently, a point-particle DNS of this case was performed in a configuration that contained roughly 10 5 particles (Vreman 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gore & Crowe (1989) compiled results from a variety of experiments which suggest that solid particles can act either to dissipate or to enhance turbulence energy depending on the diameter of the particles relative to the integral lengthscale of the flow; however, no conclusions could be drawn as to the magnitude of the modulation. Kulick, Fessler & Eaton (1994) conducted experiments of a fully developed channel flow with solid particle mass loadings as large as 80%. It was observed that the fluid turbulence intensity was attenuated by the particles; however, the mean fluid velocity profile remained essentially unaltered for all cases.…”
Section: Introductionmentioning
confidence: 99%
“…They also found an increased isotropy of the velocity fluctuations of the water flow and from that concluded that the presence of the particles modifies the dynamics of the fluid turbulence, not only by exchange of momentum and energy, but also due to a possible influence of the particles on the flow structure. Kulick et al (1994) measured turbulence modification by 50 and 90 μm glass beads and 70 μm copper particles in a pipe flow and found that the copper particles reduced the carrier phase turbulence levels while the glass beads had little effect. Fessler & Eaton (1999) performed similar measurements in a backward facing step and found that turbulence reduction was a function of particle Stokes and Reynolds number and the specific flow regime.…”
Section: Introductionmentioning
confidence: 99%